Tourism Development Strategy at Minang Rua Beach, Kelawi Village using Differentiation Strategy - Lolita, Allyen Jeslyn; Barusman, Muhammad Yusuf Sulfarano (East Asian Journal of Multidisciplinary Research, 2024)
Tourism development is an important effort to improve the economy of a region. One of the tourist attractions that has natural and cultural potential is Minang Rua Beach. Minang Rua Beach is a tourist destination that has its uniqueness to find great opportunities for sustainable tourism development. Minang Rua Beach implements a strategy for tourism development, namely a differentiation strategy. The differentiation strategy has been recognized as an effective approach in attracting the attention of tourists and differentiating tourism destinations from others. This research aims to analyze and describe how differentiation strategies are applied in tourism development. The research method used was descriptive qualitative, data was collected through observation, interviews, and documentation. Based on observations at Minang Rua Beach and interviews with Minang Rua Beach Managers who are members of the Tourism Awareness Group (POKDARWIS) as well as tourists who come to this tourist spot, Minang Rua Beach shows unique natural and cultural uniqueness. Minang Rua Beach has become the main pawn in implementing differentiation strategies such as natural beauty, cultural diversity, or exclusive activities. Researchers found that marketing efforts that emphasize the uniqueness and specialness of destinations have succeeded in attracting market attention.